Comparative study on the pretreatment of algae-laden water by UV/persulfate, UV/chlorine, and UV/H2O2: Variation of characteristics and alleviation of ultrafiltration membrane fouling. (1st July 2019) - Wan, Ying; Xie, Pengchao; Wang, Zongping; Ding, Jiaqi; Wang, Jingwen; Wang, Songlin; Wiesner, Mark R.
Abstract: In this study, ultraviolet based advanced oxidation processes (UV-AOPs) including UV/persulfate (UV/PS), UV/chlorine, and UV/H2 O2 were employed to alleviate ultrafiltration membrane fouling during the treatment of algae-laden water. The results show that UV/PS pretreatment exhibited the best performance on fouling control, followed by the UV/H2 O2 pretreatment. The fouling mitigation performance improved with the increase of oxidant dose. However, UV/chlorine pretreatment aggravated membrane fouling, and the irreversible fouling resistance increased by five times compared with that of raw water. The dissolved organic carbon (DOC) in the algae-laden solution was reduced after UV/PS pretreatment, while either UV/chlorine or UV/H2 O2 pretreatment had little influence on the DOC of feed water. UV/PS and UV/H2 O2 pretreatments were effective in the degradation of fluorescent compounds, thus reducing the deposition of organic matter on the membrane surface. Additionally, the decreased concentration of hydrophobic organics, algal cells, and debris in feed water after UV/PS pretreatment was also contributed to the fouling alleviation. The aggravated irreversible fouling after UV/chlorine pretreatment was probably ascribed to the increased accumulation of hydrophobic fractions in the membrane pores. Modeling result indicates that membrane fouling during the filtration of raw algae-laden water was dominated by intermediate blocking and cake filtration mechanisms. Both UV/PS and UV/H2 O2 pretreatments transformed the combined fouling mechanism into standard blocking, while UV/chlorine pretreatment aggravated the pore blocking in the initial filtration period. Graphical abstract: Image 1 Highlights: UV/PS pretreatment effectively mitigated fouling caused by algae-laden water. UV/H2 O2 pretreatment reduced fouling at high H2 O2 dose. UV/chlorine pretreatment significantly aggravated irreversible fouling. Intrinsic mechanisms of membrane fouling after UV-AOPs pretreatment were proposed.